2019
DOI: 10.1080/17453674.2019.1675928
|View full text |Cite
|
Sign up to set email alerts
|

Femoral and pelvic osteotomies for severe hip displacement in nonambulatory children with cerebral palsy: a prospective population-based study of 31 patients with 7 years’ follow-up

Abstract: Background and purpose — There is no consensus regarding the optimal treatment of hip displacement in children with cerebral palsy (CP). This prospective study assessed the outcome of femoral and pelvic osteotomies for severe hip displacement in nonambulatory children and analyzed prognostic factors for outcome.Patients and methods — 31 nonambulatory children (20 boys), recruited from a population-based screening program, consecutively underwent unilateral (23) or bilateral (8) osteotomies and bilateral soft-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 30 publications
2
35
0
3
Order By: Relevance
“…A recent study on non-ambulatory patients with severe hip displacement showed that hip surgery had a good effect on hip pain. 20 In particular, patients with unilateral subluxation combined with pelvic obliquity should be offered surgical treatment, including femoral and/or pelvic osteotomies, if their general condition allows such major surgery. In patients with painless bilateral complete dislocation, surgical treatment to relocate hips is hardly indicated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study on non-ambulatory patients with severe hip displacement showed that hip surgery had a good effect on hip pain. 20 In particular, patients with unilateral subluxation combined with pelvic obliquity should be offered surgical treatment, including femoral and/or pelvic osteotomies, if their general condition allows such major surgery. In patients with painless bilateral complete dislocation, surgical treatment to relocate hips is hardly indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Further, hip subluxation was categorized as mild (migration percentage 33–39%), moderate (migration percentage 40–49%), and severe (migration percentage 50–89%). Pelvic obliquity was measured as the angle between the horizontal line and the line between the lowest points of the pelvic bones on the right and left side 20 . Further, the presence of deformities of the proximal femur (flattening or deformity of the femoral head and marked shortening or pronounced varus of the femoral neck) was assessed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some literature noted that kinematic and kinetic parameters 8 of gait in most patients undergoing FDO were effectively maintained during the follow-up of 5 to 10 years postoperatively [19,124,125], the adverse effect of postoperative complications has been incessantly reported, such as pelvic tilt and recurrence of internal hip rotation and hip subluxation [126][127][128][129]. For symptomatic patients with subluxation or dislocation, which were associated with deformity of the femoral head or degenerative changes for blocking hip reconstruction, salvage treatment, including pelvic osteotomy, arthrodesis, and arthroplasty, should be considered [130,131]. Pelvic osteotomy is performed using various methods, including Pemberton osteotomy, Chiari pelvic osteotomy, Salter innominate osteotomy, and Dega osteotomy [91,132,133], among which the Dega osteotomy has been widely adopted for the treatment of hip dislocation of CP [134,135].…”
Section: Hip Surgerymentioning
confidence: 99%
“…Currently, most studies report that multilevel surgery (FDO or open reduction associated with pelvic osteotomy), better than single-level surgery in a therapeutic outcome, can be available to reduce the recurrence rate of hip dislocation. However, serious complications have led to more concerns, such as heterotopic ossification and avascular necrosis of the femoral head [130, 131, 136, 137]. Arthrodesis and prosthetic interposition arthroplasty have been gradually applied to the treatment of hip dislocation of the patients with CP.…”
Section: Surgical Treatmentmentioning
confidence: 99%